COMBINED TREATMENT OF A PATIENT WITH A TESTICULAR GERM CELL TUMOR WITH SIGNS OF MULTIPLE ORGAN FAILURE - T. V. Ustinova; L. V. Bolotina; A. A. Fedenko; H. S. Gevorgyan; A. A. Paichadze; A. L. Kornietskaya; N. V. Vorobyev; K. M. Nushko; A. S. Kalpinskiy; A. A. Kachmazov; K. M. Isaeva (Исследования и практика в медицине)
Testicular cancer is a rare malignant tumor. In the structure of general cancer incidence, this nosology accounts for about 1–1.5% of cases. Among this pathology, about 90–95% is due to testicular germ cell tumors. Currently, testicular cancer is a potentially treatable solid tumor with a 10-year survival rate of more than 95% upon timely diagnosis and proper treatment. In this regard, early diagnosis and treatment of this pathology is an urgent task today. The article presents a clinical observation of the treatment of a patient with a testicular germ cell tumor. The presented clinical case demonstrates the successful conduct of neoadjuvant chemotherapy and further orchifuniculectomy in the presence of distant metastases namely in case of a non-seminomic form of a testicular germ cell tumor. The approach to treating patients with testicular tumors must be individualized and take into account both the potential gain and the potential risks of the treatment being performed.